PP.07.11: IGNORED AND NEGLECTED CAUSE OF ACUTE LEFT HEART FAILURE. PHOSPHORUS DEFICIENCY IN MASSRY'S PHOSPHATE DEPLETION SYNDROME. GIVING I.V. OR ORAL PHOSPHATE MIGHT SAVE THE LIVES. (June 2015) - Keskek, S.O.; Sagliker, Y.; Kirim, S.; Icen, Y.K.; Yildirim, A.; Paylar, N.
Abstract : Objective: In this study we investigated serum phosphorus levels in patients with acute left heart failure. Design and method: A total of 215 participants, 115 patients with acute left heart failure and 100 controls, were enrolled in the study. Patients applied to emergency room with the complaints of heart failure were assessed by echocardiography. Ejection Fraction (EF) levels lower than 50% were accepted as heart failure. Patients with renal disorders, hyperparathyroidism, chronic hearth failure, alcoholism, intake of medications that alter phosphorus level were excluded. Mean phosphorus levels of each group were measured and compared each other. SPSS 12.0 package program (SPSS Inc., Chicago, Illinois) was used for statistical analysis. Chi square test was used to compare categorical measures between the groups. Mann Whitney U or T test was used for comparison of numerical measurements between the two groups. Level of statistical significance was considered as 0.05 in all tests. Results: There were 148 (69%) women and 67 (31%) men in the present study. The mean age was52.6 ± 12.1 years. Demographic characteristics of participants were not significantly different between the groups. Mean EF levels of groups were 40.8 ± 6.3 in phosphate depleted group and 60.0 ± 9.7 in controls, respectively. The difference between two groups was statistically significant (P < 0.001). Mean phosphorus levels were 3.0 ± 1.1 in phosphate depleted groups and 4.2 ± 0.7 mg/dl respectively. There was statistically significant difference (P = 0.041) (Table 1). Conclusions: Phosphorus is a major intracelluler constituent. The deficiency of phosphorus can cause a variety of signs and symptoms. Myocardial creatine phosphate, ATP, and ADP levels reduce in case of phosphate deficiency. In addition to these, mitochondrial and myofibrillar creatine phosphokinase activities also reduces. Alterations occur in mitochondrial oxygen consumption, acid-extractable phospholipid precursors, and mitochondrial oxidation of long chain fatty acids due to phosphate depletion. All these effect heart muscles and can cause heart failure. Consequently phosphorus levels should be controlled in patients with acute left heart failure. Phosporus supplementation may be a supportive Sine Qua Non treatment.And it may save lives. Figure. No caption available. Table 1: phosphorus levels in study and control group. Studygroup (HF +) Control group (HF -)P Study group